Investigation of solar radiation distribution over three zones north, middle and south of Jordan - S. Alrwashdeh, Saad; M. Alsaraireh, Falah (International Journal of Engineering and Technology, 2018)
Solar energy considers as the best alternative energy source in Jordan as the solar radiation average is high in Jordan which is between 4 and 8 kWh/m2. The average solar radiation is connected with an energy potential of 1400 to 2300 GWh per year. Electricity is the main source of energy used in Jordan as all daily applications rely on it such as heating, cooling, lighting, etc. For that studying solar radiation carefully is an essential issue to ensure the availability of the power when it needed. In this study, a solar radiation distribution is provided of three main zones in Jordan north, middle and south.
Keywords: Energy; Electrical Demand; Solar Radiation Distribution; Solar Energy.